2020
DOI: 10.1144/sp500-2019-201
|View full text |Cite
|
Sign up to set email alerts
|

Effects of rotational submarine slump dynamics on tsunami genesis: new insight from idealized models and the 1929 Grand Banks event

Abstract: Sediment slumps are known to have generated important tsunamis such as the 1998 Papua New Guinea (PNG) and the 1929 Grand Banks events. Tsunami modellers commonly use solid blocks with short run-out distances to simulate these slumps. While such methods have the obvious advantage of being simple to use, they offer little or no insight into physical processes that drive the events. The importance of rotational slump motion to tsunamigenic potential is demonstrated in this study by employing a viscoplastic lands… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 46 publications
0
20
0
Order By: Relevance
“…In this study, we treat the 2018 Anak Krakatoa flank collapse as a depth-averaged visco-plastic Herschel-Bulkley type flow with the landslide model BingClaw (Løvholt et al 2017;Kim et al 2019;Vanneste et al 2019). BingClaw has previously been successfully used for modelling clay-rich materials of the largest submarine landslides of the world such as Traenadjupet and Storegga (Løvholt et al 2017;Kim et al 2019), and the 1929 Grand Banks landslide (Løvholt et al 2018;Zengaffinen et al 2020). Here we use BingClaw for modelling the volcanic rockslope landslide failure dynamics.…”
Section: The 2018 Anak Krakatoa Eventmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we treat the 2018 Anak Krakatoa flank collapse as a depth-averaged visco-plastic Herschel-Bulkley type flow with the landslide model BingClaw (Løvholt et al 2017;Kim et al 2019;Vanneste et al 2019). BingClaw has previously been successfully used for modelling clay-rich materials of the largest submarine landslides of the world such as Traenadjupet and Storegga (Løvholt et al 2017;Kim et al 2019), and the 1929 Grand Banks landslide (Løvholt et al 2018;Zengaffinen et al 2020). Here we use BingClaw for modelling the volcanic rockslope landslide failure dynamics.…”
Section: The 2018 Anak Krakatoa Eventmentioning
confidence: 99%
“…The Herschel-Bulkely flow exponent n is 0\n\1 for shear-thinning materials. During preliminary tests, it was found that n is not important for the tsunami generation (Zengaffinen et al 2020). We employ n ¼ 0:5.…”
Section: Geometrical and Geotechnical Inputmentioning
confidence: 99%
“…To this end, a range of factors controls the tsunami genesis, as discussed extensively in the literature, e.g. (Yavari-Ramshe and Ataie-Ashtiani 2016; Løvholt et al 2015;Fritz et al 2003;Grilli and Watts 2005;Harbitz et al 2006;Haugen et al 2005;Heller et al 2008;Løvholt et al 2005;Ruffini et al 2019;Ward 2001;Watts 2000;Zengaffinen et al 2020), and we only provide a simplified review here, presenting a few essential findings:…”
Section: Introductionmentioning
confidence: 99%
“…Because tsunami genesis is tightly linked to landslide acceleration as well as rate of mobilization of the landslide volume (e.g., Løvholt et al, 2005), quantifying the rate and nature of the slope failure is important. Just a few studies discuss the effect of initial failure rate on tsunami generation (e.g., Trapper et al, 2015;Germanovich et al, 2016;Puzrin et al, 2016) and related aspects such as remoulding and cascading failures on the landslide tsunami generation (e.g., Løvholt et al, 2017;Kim et al, 2019;Zengaffinen et al, 2020). How to include these factors and their associated probabilities in PTHA is not resolved.…”
Section: Limited Constraints On Landslide Dynamics and Materials Behavior (L3)mentioning
confidence: 99%
“…Incorporating time-dependent and moving sources, be it earthquakes (e.g., Ulrich et al, 2019a), landslides (e.g., Løvholt et al, 2015b) or volcanoes, will involve much higher computational burden. How to limit the number of source time steps for time-dependent source modeling is sparsely studied (e.g., Zengaffinen et al, 2020). For landslide tsunamis, closed-form models (e.g., Cecioni and Bellotti, 2010) represent a simple alternative but can introduce biases when conveyed to real geographical settings, due to oversimplification or inadequacy for the real situation.…”
Section: Tsunami Generation (H2)mentioning
confidence: 99%